Effect of Zinc and Molybdenum on the Growth and Yield of Garden Pea (Pisum sativum L.) - Alam, Ishrat; Paul, Alok Kumar; Sultana, Saima; Bithy, Parvin Akter (International Journal of Bio-resource and Stress Management, 2020)
The experiment was conducted at the farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from December 2015 to March 2016 to study the effect of zinc and molybdenum on the growth and yield of garden pea. The variety BARI Motorshuti-1 was used as the test crop. Two factors experiment as, Factor A: Levels of zinc (3 levels)- Zn0: 0 kg Zn ha-1, Zn1.5: 1.5 kg Zn ha-1 Zn3.0: 3.0 kg Zn ha-1 and Factors B: Levels of molybdenum (3 levels)- Mo0: 0 kg Mo ha-1, Mo0.3: 0.3 kg Mo ha-1, Mo0.6: 0.6 kg Mo ha-1 was laid out in Randomized Complete Block Design (RCBD) with three replications. In case of different levels of zinc, the tallest plant, maximum number of pods plant-1, the highest green pod yield hectare-1 were recorded from Zn3.0, whereas the shortest plant, the lowest green pod yield hectare-1 were found from Zn0. For different levels of molybdenum, the tallest plant, the highest green pod yield hectare-1, was found from Mo0.6, while the shortest plant, the minimum number of pods plant-1, the lowest green pod yield hectare-1, was recorded from Mo0. Due to the interaction effect of different levels of zinc and molybdenum, the tallest plant, the highest green pod yield hectare-1 were found from Zn3.0Mo0.6 and maximum number of pods plant-1 found from Zn1.5Mo0.6. The shortest plant, the minimum number of pods plant-1, the lowest green pod yield hectare-1 were found from Zn0Mo0.